Analysis of The Role of Banking, Local Government, and Private Investment on Tourism Development in Pamekasan Regency - Dewi Ayu Lestari; Aprilina Susandini (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The aim of this research is to examine and analyze the relationship between the role of banking, local government, and private investment in the development of the tourism. Quantitative method and primary data with multiple linear regression analysis. The research location is tourism destination in Pamekasan Regency, East Java. This research also used simple random sampling as data collection method and obtained 15 tourism samples with 60 respondents. Data analysis was carried out using the SPSS version 25 application. The results of this research show that banking has a positive and significant effect on tourism development in Pamekasan Regency, local government has no effect on tourism development in Pamekasan Regency, private investment has no effect on tourism development in Pamekasan Regency, and also banking, local government, and private investment simultaneously have a positive and significant influence on tourism development in Pamekasan Regency. This research suggests that banks, local governments and private investment are supposed to create a harmonious and equal synergy to realize tourism development in Pamekasan Regency.